Quality, value, satisfaction and loyalty amongst race groups: A study of customers in the South African fast food industry - N. S. Terblanche; C. Boshoff (South African Journal of Business Management, 2010)
The retention of customers has become a key concern for many businesses. Various drivers of loyalty such as satisfaction, loyalty and commitment have, over time, been studied with the objective to improve customer retention. This study reports on the empirical findings in respect of the relationships between various dimensions of a loyalty model for the South African fast food sector and considers differences amongst race groups in respect of perceived quality, value, satisfaction and loyalty.Respondents in this empirical study were consumers drawn randomly from the seven major metropolitan areas of South Africa. The respondents are all customers of a national firm in the South African fast food sector and they were required to respond to items from (mostly) the American Customer Satisfaction Index (ACSI) scales. The empirical findings provide support for the theoretical model proposed but there is not much difference in how the various race groups' loyalty intentions are shaped.
Keywords: 650